THE EFFECTS OF IRON DEFICIENCY ON NEUROTRANSMISSION AND COGNITIVE FUNCTION: A LITERATURE REVIEW - Marta Ewelina Lis; Katarzyna Rumianek-Fidziukiewicz; Kornelia Kaźmierkiewicz; Martyna Chojnacka; Ewa Ciechańska; Kornel Kapuśniak; Weronika Suszczyńska; Zuzanna Lasota; Weronika Domańska; Agata Zając (International Journal of Innovative Technologies in Social Science, 2025)
Iron, though required by the body in only trace amounts, is quietly indispensable for the healthy maturation and continued function of the brain. Its passage into the central nervous system is no accident; rather, it is subject to rigorous control, with the blood–brain barrier’s transferrin receptor system acting as a gatekeeper. When this delicate equilibrium is disturbed—whether by deficit or surplus—the consequences are far-reaching. Neuronal signalling falters, mitochondria become less efficient, and measurable drops in cognitive performance begin to appear. Among the neurotransmitter networks, the dopaminergic, serotonergic, and glutamatergic pathways seem especially sensitive to fluctuations in iron status, and their impairment is most evident in memory, learning, and behaviour. Infants and children, along with pregnant women and patients contending with chronic illness, are particularly vulnerable; for some, these neurodevelopmental effects may linger long after the original insult. While supplementing iron frequently reverses the deficiency, an overzealous approach can tip the scales toward toxicity. The art of clinical management lies in tailoring iron repletion to individual needs, ensuring robust neurodevelopment without courting the hazards of excess.